2021
DOI: 10.37128/2707-5826-2021-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Selection Value of Soybean Varieties for Growing in Different Soil and Climate Conditions of Ukraine

Abstract: Our research purpose is to evaluate the genotypes potential and soybeans selection from the standpoint of the potential of ontogenetic adaptation, taking into account the complex of their economically valuable personalities and properties, as well as with a positive reaction to the improvement of growing conditions. Varieties have been differentiated according to the level of ecological potential according to their reaction to growing conditions in different soil and climatic conditions of research. Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The field research was carried out according to the generally accepted methods (Biliavska et al, 2021). The main method of creating the initial material for soybean breeding was used, namely intraspecific hybridization followed by individual selection among hybrid offspring.…”
Section: Methodsmentioning
confidence: 99%
“…The field research was carried out according to the generally accepted methods (Biliavska et al, 2021). The main method of creating the initial material for soybean breeding was used, namely intraspecific hybridization followed by individual selection among hybrid offspring.…”
Section: Methodsmentioning
confidence: 99%
“…Balanced use of nitrogen, phosphorus and potash fertilisers is an important factor for maximising crop yields and achieving the desired quality. The study by researchers (Kyryliuk et al, 2020;Biliavska et al, 2021;Kotelnytska et al, 2021) confirmed the improvement of the nutrient regime of the arable soil layer, optimisation of its agrophysical and water-physical indicators by applying organic and mineral fertilisers, which are mineralised by soil microorganisms and provide plants with available nutrients. The positive effect of optimising potato fertiliser on the yield and quality of tubers was noted in the works of many researchers.…”
Section: Introductionmentioning
confidence: 94%
“…Scholars of the National Academy of Agrarian Sciences of Ukraine have determined the varietal differences of leguminous plants in terms of the intensity of biological fixation and on their basis, using biotechnology, genetics and breeding, more than 70 varieties of leguminous crops have been created, including 44 varieties of a new generation, included in the State Register of Plant Varieties Suitable for Dissemination in Ukraine, which are characterized by an increased intensity of biological fixation of nitrogen in main agricultural regions (Petrychenko et al, 2013;Biliavska et al, 2021;Mazur et al, 2023).…”
Section: Introductionmentioning
confidence: 99%